MicroRNA-223 Regulates the Development of Cardiovascular Lesions in LCWE-Induced Murine Kawasaki Disease Vasculitis by Repressing the NLRP3 Inflammasome - Maruyama, Daisuke; Kocatürk, Begüm; Lee, Youngho; Abe, Masanori; Lane, Malcolm; Moreira, Debbie; Chen, Shuang; Fishbein, Michael C.; Porritt, Rebecca A.; Noval Rivas, Magali; Arditi, Moshe (Frontiers in Pediatrics, 2021)
Kawasaki disease (KD), an acute febrile childhood illness and systemic vasculitis of unknown etiology, is the leading cause of acquired heart disease among children. Experimental data from murine models of KD vasculitis and transcriptomics data generated from whole blood of KD patients indicate the involvement of the NLRP3 inflammasome and Interleukin-1 (IL-1) signaling in KD pathogenesis. MicroRNA-223 (miR-223) is a negative regulator of NLRP3 activity and IL-1β production, and its expression has been reported to be upregulated during acute human KD, however the specific role of miR-223 during KD vasculitis remains unknown. Here, using the Lactobacillus casei cell wall extract (LCWE) murine model of KD vasculitis, we demonstrate increased miR-223 expression in LCWE-induced cardiovascular lesions. Compared with control WT mice, LCWE-injected miR-223-deficient mice (miR223–/y) developed more severe coronary arteritis and aortitis, as well as more pronounced abdominal aorta aneurysms and dilations. The enhanced cardiovascular lesions and KD vasculitis observed in LCWE-injected miR223–/y mice correlated with increased NLRP3 inflammasome activity and elevated IL-1b production, indicating that miR-223 limits cardiovascular lesion development by downmodulating NLRP3 inflammasome activity. Collectively, our data reveal a previously unappreciated role of miR-223 in regulating innate immune responses and in limiting KD vasculitis and its cardiovascular lesions by constraining the NLRP3 inflammasome and the IL-1b pathway. These data also suggest that miR-223 expression may be used as a marker for KD vasculitis pathogenesis and provide novel therapeutic target.